UPAYA MENINGKATKAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN INDEX CARD MATCH DI KELAS V SD NEGERI 60/II MUARA BUNGO KECAMATAN RIMBO TENGAH KABUPATEN BUNGO - Muhammad Hakiki; Debby Permata Cinta (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2021)
The problem in this study is the low value of the process and results of learning mathematics in class V SD Negeri 60 / II Muara Bungo, this is evidenced by the results of observations with the class V homeroom teacher. The aim of this research is to describe the application of the index card match model in the learning process. learners and students' thinking skills. This type of research is classroom action research (PTK). This study consisted of 2 cycles, each cycle carried out through 4 stages, namely planning, action, observation and reflection and consisted of 2 meetings. The results of the application of the index card match model were carried out by the following steps: (1) Delivering objectives and motivating students, (2) Presenting information, (3) Organizing students into study groups, (4) Guiding students in study groups, ( 5) evaluation, so as to improve the process and results of learning mathematics in class V SD Negeri 60 / II Muara Bungo with the percentage of teacher teaching activities, namely 60% in cycle I meeting I, 75% in cycle I meeting II, 80% in cycle II meeting I, 87% cycle II at the second meeting. As well as an increase in the learning process of students as indicated by learning activities by 58% in the first cycle of meeting I, 70% in the first cycle of the second meeting, 75% in the second cycle of the first meeting, 80% in the second cycle of the second meeting, and the percentage of students' learning completeness. from pre-action 43% as many as 13 people who reached KKM, increased to 53% as many as 16 people who reached KM, increased to 80% as many as 24 people who reached KKM.